On optimal NMO and generalised Dix equations for velocity determination and depth conversion - Ayman N Qadrouh, José M Carcione, Marco AB Botelho, Zuhar Zahir, . (2014)
he classical Earth model used to process seismic data assumes plane layers and a velocity analysis based on a hyperbolic approximation of the reflection events, where basically one parameter (the stacking velocity) is used to perform the normal move-out (NMO) correction to obtain the stacked section.